The Use of Natural Dyes from Beetroot Skin Extract (Beta Vulgaris) as Teaching Material on Cell Division for Senior High School Students - Adilla Nur Azizah; Putri Agustina; Suparti Suparti; Alanindra Saputra; Yasir Sidiq (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2020)
One of the Basic Competencies (KD) in Biology for Indonesian Senior High School is KD 4.12 which reads "Presents observations of the process of mitosis in the onion root and determines the phases it finds". Based on the basic competency test, students are required to have skills in making and observing mitotic preparations of plant tissue with at least using onion. Observation of mitotic division in plant tissues requires skill in making preparations. Making preparations in observing cells and tissues of plants or animals needs staining. Dyes often used in lab work are synthetic dyes. One of the synthetic dyes commonly used is safranin. However, safranin is quite expensive. This limitation requires teachers to look for alternatives to synthetic dyes that are easily found at a more affordable price, namely with natural dyes. One of the plants that has the potential to overcome this issue is beetroot (Beta vulgaris). The purpose of this study was to determine the quality of plant tissue preparations (Allium cepa) stained with beetroot skin (Beta vulgaris) as a natural coloring agent. The research method used was an experimental method with a Completely Randomized Design consisting of two factors, namely the staining time (1 hour, 2 hours, and 3 hours) and the type of solvent (aquades and citric acid 10%). The results of the study were analyzed with qualitative descriptive methods which included contrast and clarity of the preparations. Based on the results of the study, the quality of Allium cepa root preparations using beetroot (Beta vulgaris) skin extract with variations in the type of solvent and duration of staining showed good results on the staining time of 1 hour and 2 hours. The staining time of the preparations can affect the contrast and clarity of the preparations.